Wreaking “Havoc” on Smoking: Social Branding to Reach Young Adult “Partiers” in Oklahoma - Fallin, Amanda (Am J Prev Med, 2015)
BACKGROUND: More than 25% of young adult Oklahomans smoked cigarettes in 2012. Tobacco marketing campaigns target young adults in social environments like bars/nightclubs. Social Branding interventions are designed to compete directly with this marketing. PURPOSE: To evaluate an intervention to reduce smoking among young adult “Partiers” in Oklahoma. The Partier social subculture was described as follows: attendance at large nightclubs, fashion consciousness, valuing physical attractiveness, and achieving social status by exuding an image of confidence and financial success. DESIGN: Repeated cross-sectional study with three time points. SETTING/PARTICIPANTS: Randomized time location survey samples of young adult Partier bar and club patrons in Oklahoma City (Time 1 [2010], n=1,383; Time 2 [2011], 1,292; and Time 3 [2012], 1,198). Data were analyzed in 2013. INTERVENTION: The “HAVOC” Social Branding intervention was designed to associate a smoke-free lifestyle with Partiers’ values, and included events at popular clubs, brand ambassador peer leaders who transmit the anti-tobacco message, social media, and tailored anti-tobacco messaging. MAIN OUTCOME MEASURES: Daily and nondaily smoking rates, and binge drinking rates (secondary). RESULTS: Overall, smoking rates did not change (44.1% at Time 1, 45.0% at Time 2, and 47.4% at Time 3 (p=0.17), but there was a significant interaction between intervention duration and brand recall. Partiers reporting intervention recall had lower odds of daily smoking (OR=0.30 [0.10, 0.95]) and no difference in nondaily smoking, whereas among Partiers without intervention recall had increased odds of smoking (daily AOR=1.74 [1.04, 2.89], nondaily AOR=1.97 [1.35, 2.87]). Among non-Partiers, those who recalled HAVOC reported no difference in smoking, and those who did not recall HAVOC reported significantly increased odds of smoking (daily AOR=1.53 [1.02, 2.31], nondaily AOR=1.72 [1.26, 2.36]). Binge drinking rates were significantly lower (AOR=0.73 [0.59, 0.89]) overall. CONCLUSIONS: HAVOC has potential to affect smoking behavior among Oklahoma Partiers without increasing binge drinking.